Design strategy and techno-economic optimization for hybrid ground heat exchangers of ground source heat pump system. (August 2022) - Zhou, Kun; Mao, Jinfeng; Zhang, Hua; Li, Yong; Yu, Xiaojun; Chen, Fei; Li, Min
Highlights: Heat transfer numerical model and techno-economic model of GSHP system were combined. Accurate design strategy of hybrid GHEs of GSHP system was put forward. Shave factor, building load distribution scheme, and HyGHE size were optimized. Impacts of parameters affecting the optimal design of hybrid GHEs were quantified. Abstract: This study aimed to formulate an accurate design strategy for hybrid ground heat exchanger (HyGHE) of ground source heat pump system and optimize HyGHE size based on techno-economic analysis. First, to analyze the thermal performance of the HyGHE system, a detailed heat transfer numerical model of borehole heat exchanger and horizontal ground heat exchanger was proposed. Then, a novel techno-economic model was employed to assess the economic efficiency of the foregoing system. Subsequently, the design optimization model of the HyGHE system was developed to determine the optimal shave factor ( α and β ), building load distribution scheme, and HyGHE size. Finally, sensitivity analyses were implemented to determine the optimal design under different conditions. The results reveal that the costs of borehole drilling, pipe, and equipment account for approximately 80% of total capital investments of the HyGHE system. The system initial costs increase with α and can reach 91, 385.11 CNY when α = 1.00. In contrast, its annual operational costs first decrease and then increase with increasing α . For the fundamental case, the thermal and economic performance levels of the HyGHE system improve with decreasing α . The optimal design is more sensitive to the unit prices of borehole drilling, pipe, and excavation.